Quo Vadis of the Constitutional Court in Resolving Disputes Over Regional Election Results After Constitutional Court Decision No. 85/PUU-XX/2022 - Yarni, Meri; Najemi, Andi; Suhermi, Suhermi; Davega Prasna, Adeb; Rizki Amanda, Khofifah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research aims to determine and analyze the Legal Politics of the Constitutional Court in deciding disputes over the results of regional election disputes in Indonesia. The authority of the Constitutional Court in resolving disputes over the results of Regional Election has yet to be regulated in the 1945 Constitution of the Republic of Indonesia. The authority of the Constitutional Court to decide disputes over the results of general election described in Article 24C paragraph (1) is different from regional election. This has been explained in the decision of the Constitutional Court Number 97/PU U-XI-2013, which states that the election and regional election regimes are different and the authority to decide disputes over election results is not the authority of the Constitutional Court but the authority of a particular judicial body. This research used normative juridical research methods, where library law was studied by examining library materials. Then, the collected materials are analyzed in a descriptive qualitative manner. The study results concluded that the Constitutional Court has the authority to permanently examine, decide, and resolve disputes over election results by the Constitutional Court Number 85 / PUU-XX / 2022 decision. There is no longer a distinction between the election regime and the election. With the decision of the Constitutional Court Number 85 / PUU-XX / 2022, the authority of the Constitutional Court becomes more precise and more substantial because of the binding legal certainty.